Breast Cancer Risk Perception and Lifestyle Behaviors among White and Black Women with a Family History - Spector, Denise (2009)
Little is known about relationships between a positive family history of breast cancer, perception of risk, and lifestyle behaviors. This qualitative study explored factors involved in formulation of perceived breast cancer risk and the association between risk perception and lifestyle behaviors in white and black women with a family history of breast cancer. Eligible participants were North Carolina residents in the Sister Study, a nationwide study of environmental and genetic risk factors for breast cancer among women aged 35 to 74 who have at least one sister diagnosed with breast cancer. Personal interviews were conducted with thirty-two women, twenty white and twelve black. While many had a heightened sense of risk and perceived family history as a main risk factor, 16% considered themselves at low or average risk for breast cancer and Gail risk scores did not correspond to perceived risk. Many women were unaware of associations between lifestyle behaviors and breast cancer risk. Eleven women, six black and five white, reported making healthy lifestyle changes because of family history; dietary change was most frequently reported. These findings may be important for future developers of breast cancer education programs for both white and black women with a family history of breast cancer.